Antimicrobial effect of seaweeds against oral-borne pathogens: a review - Zamimi, Nurul Najwa; Ab. Halim, Noorhazayti; Md Mustafa, Md Muziman Syah; Darnis, Deny Susanti; Che Musa, Muhd Firdaus; Yusof, Firdaus (2020)
Dental caries is known as the most common and preventable dental disease. This multifactorial disease has been found to be a major concern worldwide. This dental caries has been proved to be caused by the presence of oral pathogen. Seaweeds show many health-promoting effects, including antimicrobial, anti-inflammatory, anti-oxidative and anti-cancer properties. The versatility of the seaweed has attracted many researchers to use seaweed extracts as alternative treatment against multiple diseases. However, little attention has been paid to the application of antimicrobial properties of seaweed against oral pathogenic microorganisms. The substances isolated from red, brown and green seaweeds showing potent antimicrobial activity are polysaccharides, phlorotannins, pigments, fatty acids, lectins, terpenoids, alkaloids and halogenated compounds. Current research is shifting into fully grasping the antimicrobial potential of seaweeds against oral microbes that cause dental caries or periodontal disease. Hence, this mini-review will highlight the antimicrobial properties of three types of seaweed species (red, brown, and green) against selected oral pathogenic microorganisms.